U-blade gamma 3 vs. gamma 3 nails for intertrochanteric hip fracture: Meta-analysis - Mariscal, Gonzalo; Lorente, Rafael; Barrios, Carlos (Frontiers in Surgery, 2022)
Background and Objective Intertrochanteric fracture is a growing problem in the traumatology department. The use of intramedullary devices has increased, representing the first treatment option in intertrochanteric fractures. U-Blade devices appeared to avoid rotation of the femoral head over the femoral neck. The aim of this study was to conduct a meta-analysis of the surgical treatment of intertrochanteric fractures comparing in terms of safety and efficacy the U-Blade Gamma 3 nail vs. the conventional Gamma 3 nail. Methods A literature search for intertrochanteric fracture 31A1–31A3 according to the AO foundation/orthopaedic trauma association (AO/OTA) classification was performed. Baseline characteristics of each article were obtained; radiological outcomes were tip apex distance (TAD), sliding distance (mm), cut-out rate, and lateralization rate. Surgery time (min) was also recorded. A meta-analysis was performed with ReviewManager 5.4. Results Five retrospective studies (n = 993 patients) were included. With respect to TAD and sliding distance, there were no differences between two groups [mean difference (MD) 0.47, 95% confidence interval (CI), −0.46 to 1.40] and (MD 0.39, 95% CI, 0.13–0.66). The cut-out rate and lateralization rate did not show differences between two groups (p > 0.05). Finally, surgery time was significantly higher in the U-Blade Gamma 3 group (MD −4.84, 95% CI, −7.22 to −2.46). Conclusions The use of U-Blade Gamma 3 did not show significant differences in the radiological results compared with the conventional Gamma 3 nail.